A COVID-19 Outbreak in a Rheumatology Department Upon the Early Days of the Pandemic - Romão, Vasco C.; Oliveira-Ramos, Filipa; Cruz-Machado, Ana Rita; Martins, Patrícia; Barreira, Sofia; Silva-Dinis, Joana; Mendonça-Galaio, Luís; Proença, Helena; Cristino, José Melo; Sacadura-Leite, Ema; Khmelinskii, Nikita; Romeu, José Carlos; et al. (Frontiers in Medicine, 2020)
Objectives: To describe our experience with a coronavirus disease 2019 (COVID-19) outbreak within a large rheumatology department, early in the pandemic. Methods: Symptomatic and asymptomatic healthcare workers (HCWs) had a naso-oropharyngeal swab for detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and were followed clinically. Reverse transcription polymerase-chain reaction (RT-PCR) was repeated to document cure, and serological response was assessed. Patients with risk contacts within the department in the 14 days preceding the outbreak were screened for COVID-19 symptoms. Results: 14/34 HCWs (41%; 40±14 years, 71% female) tested positive for SARS-CoV-2, and 11/34 (32%) developed symptoms but were RT-PCR-negative. Half of RT-PCR-positive HCWs did not report fever, cough, or dyspnea before testing, which were absent in 3/14 cases (21%). Mild disease prevailed (79%), but 3 HCWs had moderate disease requiring further assessment, which excluded severe complications. Nevertheless, symptom duration (28±18 days), viral shedding (31±10 days post-symptom onset, range 15-51) and work absence (29±28 days) were prolonged. 13/14 (93%) of RT-PCR-positive and none of the RT-PCR-negative HCWs had a positive humoral response, with higher IgG-index in individuals over 50 years (14.5±7.7 vs 5.0±4.4, p=0.012). Of 617 rheumatic patients, 8 (1.3%) developed COVID-19 symptoms (1/8 hospitalization, 8/8 complete recovery), following a consultation/procedure with an asymptomatic (7/8) or mildly-symptomatic (1/8) HCW. Conclusions: A COVID-19 outbreak can occur among HCWs and rheumatic patients, swiftly spreading over the presymptomatic stage. Mild disease without typical symptoms should be recognized, and may evolve with delayed viral shedding, prolonged recovery, and adequate immune response in most individuals.